A review of the flightless genus Nanotermitodius Howden, 2003 (Coleoptera: Scarabaeidae: Aphodiinae: Rhyparini) - Skelley, Paul E.; Smith, Andrew B.t.; Mora-Aguilar, Eder F. (Zootaxa, 2022)
The genus Nanotermitodius Howden, 2003 (Coleoptera: Scarabaeidae: Aphodiinae: Rhyparini) is reviewed and a new species described. Only two species are presently known in the genus, Nanotermitodius andersoni Skelley, Smith, & Mora-Aguilar, new species, and Nanotermitodius peckorum Howden, 2003, which both occur in Oaxaca, Mexico. A key and distribution map for the species are presented.